Thrombin-like Enzymes from Snake Venoms: An Updated Inventory - Pirkle, Hubert (Thrombosis and Haemostasis, 1998)
As in the previous inventory (93), the term “thrombin-like”, continues to mean direct “fibrinogen-clotting”. The present tabulation adds 32 publications to the earlier one and focuses mainly on biochemical properties. Broader treatment of these enzymes, such as medical and other biological applications, can be found in a number of review articles and chapters (9, 69, 90, 110, 118).